Tuned mass dampers for response control of torsional buildings. - Singh, Mahendra P.
This paper presents an approach for optimum design of tuned mass dampers for response control of torsional building systems subjected to bi-directional seismic inputs. Four dampers with fourteen distinct design parameters, installed in pairs along two orthogonal directions, are optimally designed. A genetic algorithm is used to search for the optimum parameter values for the four dampers. This approach is quite versatile as it can be used with different design criteria and definitions of seismic inputs. It usually provides a globally optimum solution. Several optimal design criteria, expressed in terms of performance functions that depend on the structural response, are used. Several sets of numerical results for a torsional system excited by random and response spectrum models of seismic inputs are presented to show the effectiveness of the optimum designs in reducing the system response.
Keywords: Seismic response; Response control; Torsional buildings; Tuned mass dampers; Genetic algorithms; Optimal design